FACTORS AFFECTING THE INCIDENCE OF UNWANTED PREGNANCY AMONG ADOLESCENTS: A SCOPING REVIEW - Ningsih, Ayu Ida; Adnani, Qorinah Estiningtyas Sakilah; Yuwansyah, Yeti; Dharojatin, Dora; Setyawati, Anita (Journal of Maternity Care and Reproductive Health, 2025)
Adolescent unwanted pregnancies can adversely affect individuals both physically and psychologically.  This study seeks to discover factors influencing the incidence of unintended pregnancies among adolescents during the past five years.  The research employed a scoping review methodology using the six-stage approach established by Arskey and O'Malley, utilising article searches in the Garuda, MEDLINE, and Scopus databases.  The inclusion criteria encompassed works from quantitative or qualitative research addressing the determinants of premarital pregnancy among teenagers aged 10–19 years, published in Indonesian or English between 2020 and 2024.  The review identified nine articles from South America, East Africa, South Africa, and Indonesia.  Seven primary factors contribute to unwanted pregnancies among adolescents: promiscuity, insufficient parental supervision, ignorance regarding the risks of premarital sex, the impact of pornography, sexual and emotional violence or abuse, childhood experiences of physical violence, and economic difficulties.  Many adolescent females acknowledged that a discordant connection with their parents or surroundings served as a catalyst for stress, prompting them to seek solace through premarital sexual activity.  Consequently, the role of parents is crucial in providing a secure and nurturing environment for children's cognitive and emotional development.  Additional research is required to investigate adolescents' expectations regarding parental involvement in the prevention of unintended pregnancies.